Personalized 3D printed coronary models in coronary stenting - Sun, Zhonghua; Jansen, S. (AME Publishing Company, 2019)
Background: 3D printing has shown great promise in cardiovascular disease, with reports mainly focusing on pre-surgical planning and medical education. Research on utilization of 3D printed models in simulating coronary stenting has not been reported. In this study, we presented our experience of placing coronary stents into personalized 3D printed coronary models with the aim of determining stent lumen visibility with images reconstructed with different postprocessing views and algorithms. Methods: A total of six coronary stents with diameter ranging from 2.5 to 4.0 mm were placed into 3 patient-specific 3D printed coronary models for simulation of coronary stenting. The 3D printed models were placed in a plastic container and scanned on a 192-slice third generation dual-source CT scanner with images reconstructed with soft (Bv36) and sharp (Bv59) kernel algorithms. Thick and thin slab maximum intensity projection (MIP) images were also generated from the original CT data for comparison of stent lumen visibility. Stent lumen diameter was measured on 2D axial and MIP images, while stent diameter was measured on 3D volume rendering images. 3D virtual intravascular endoscopy (VIE) images were generated to provide intraluminal views of the coronary wall and stent appearances. Results: All of these stents were successfully placed into the right and left coronary arteries but 2 of them did not obtain wall apposition along the complete length. The stent lumen visibility ranged from 54 to 97%, depending on the stent location in the coronary arteries. The mean stent lumen diameters measured on 2D axial, thin and thick slab MIP images were found to be significantly smaller than the actual size (P<0.01). Thick slab MIP images resulted in measured stent lumen diameters smaller than those from thin slap MIP images, with significant differences noticed in most of the measurements (4 out of 6 stents) (P<0.05), and no significant differences in the remaining 2 stents (P=0.19–0.38). In contrast, 3D volume rendering images allowed for more accurate measurements with measured stent diameters close to the actual dimensions in most of these coronary stents, except for the stent placed at the right coronary artery in one of the models due to insufficient expansion of the stent. Images reconstructed with sharp kernel Bv59 significantly improved stent lumen visibility when compared to the smooth Bv36 kernel (P=0.01). 3D VIE was successfully generated in all of the datasets with clear visualization of intraluminal views of the stents in relation to the coronary wall. Conclusions: This preliminary report shows the feasibility of using 3D printed coronary artery models in coronary stenting for investigation of optimal coronary CT angiography protocols. Future studies should focus on placement of more stents with a range of stent diameters in the quest to reduce the need for invasive angiography for surveillance.